Patterns of substance use among adolescents: A systematic review. (1st November 2020) - Halladay, Jillian; Woock, R.; El-Khechen, H.; Munn, C.; MacKillop, J.; Amlung, M.; Ogrodnik, M.; Favotto, L.; Aryal, K.; Noori, A.; Kiflen, M.; Georgiades, K.
Highlights: This is a systematic review of 70 studies on patterns of adolescent substance use. Typical clusters: low use, single or dual substances, moderate multi- use, high multi-use. Alcohol, cannabis, and/or tobacco characterized low, single, dual, and moderate clusters. Mental health and substance use co-occurred, but distinct patterns also emerged. Clustering methods were heterogenous and poorly reported, limiting comparability. Abstract: Purpose: This review characterizes empirically derived patterns of multiple (multi-) substance use among adolescents. A secondary objective was to examine the extent to which mental health symptomatology was included in the empirical analyses examining substance use patterns. Methods: Eligible studies included those that used cluster-based approaches, included the assessment of at least two different substances, and were based on study samples with mean ages between 11 and 18 years. 4665 records were screened including 461 studies for full-text screening. Results: 70 studies were included with common clusters being: low use, single or dual substance use, moderate general multi-use, and high multi-use. The most common patterns of single or multi-substance use were: alcohol only, alcohol with cannabis and/or tobacco, and use of alcohol, tobacco, and cannabis with and without other drugs. Lower socioeconomic status, older age, and male gender were consistent predictors of multi-use clusters. Only 37 % of studies compared differences in levels of mental health across clusters with symptoms consistently associated with a greater likelihood of multi-use. Only 29 % of studies included mental health indicators in cluster-based analyses, with over half identifying distinct mental health and substance use clusters. Fit indices in cluster analyses and measurement properties of substance use were heterogeneous and inconsistently reported across studies. Conclusions: Distinct patterns of substance use were derived but methodological differences prevented direct comparison and reduced capacity to generalize across studies. There is a need to establish standardized methodological approaches to identify robust patterns of substance use to enhance etiological, prognostic, and intervention research.